Two-field mydriatic fundus photography to assess the prevalence of macular disorder in diabetes - T.A. Avanesova; Zh.G. Oganezova; V.V. Anisimova; A.B. Baeva; D.H. Miaev (РМЖ "Клиническая офтальмология")
T.A. Avanesova1,2, J.G. Oganezova3,4, V.V. Anisimova5, A.B. Baeva3,6, D.H. Miaev1 1LLC "Liga+”, Reutov, Russian Federation 2LLC "Eye Microsurgery Center of Moscow Region", Sergiev Posad, Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation 4Research Center for Medical Genetics, Moscow, Russian Federation 5Central Clinical Hospital and Polyclinic of the Department for Presidential Affairs,   Moscow, Russian Federation 6Hospital for War Veterans No. 2, Moscow, Russian Federation Aim: to evaluate the prevalence of macular dysfunction in patients with type 1 (T1D) and type 2 diabetes (T2D) of different age and sex based on fundus photographs. Materials and Methods: this work is part of a study involving medical institutions of five cities of the Russian Federation. 367 patients with diabetes (34.88% males and 65.12% females; mean age 50.88±20.55 years) were enrolled, including 34.88% with T1D and 65.12% with T2D. The mean disease duration was 9.02±7.22 years. 58.31% of the patients had a history of hypertension and 13.08% a history of smoking. The ophthalmologists evaluated two-field fundus photographs and graded the changes as M0 (no diabetic changes in the macula) or M1 (diabetic changes in the macula). Non-diabetic changes were not included in the analysis. The presence of exudates, microaneurysms or hemorrhages within 1 DD from the center of the fovea, circular or clustered exudates in the macular area were evaluated. Results: diabetic maculopathy (DM) was found in 47 (12.81%) patients. DM was associated with diabetic retinopathy (DR) in 18 (4.90%) patients. DM was mainly observed in patients with T2D (15.90%), in women (8.45%) and bilaterally (8.17%). There were no significant differences in visual acuity between patients with and without diabetes. There was a trend towards an increased prevalence of DM in older patients with a history of T2D of 15–25 years (p>0.05). No significant differences were found in the incidence of DM and DM+DR according to glycated hemoglobin (HbA1c) levels. DM developed in 11.11% of patients with HbA1c≤7.5% and in 15.79% of patients with HbA1c>7.5% (p=0.260). There was a trend towards an increased prevalence of DM in smokers (20.83% vs. 11.60% in non-smokers, p=0.120). Elevated blood pressure did not affect the incidence of DM. Conclusion: these findings (some of which were presented in the previous publication and will be presented in the next one) emphasize the efficacy of two-field mydriatic fundus photography as a screening tool for diabetic retinopathy and maculopathy. Keywords: diabetes, retina, diabetic maculopathy, diabetic retinopathy, diabetic macular edema, screening, fundus photography, prevalence, two-field photography, risk groups. For citation: Avanesova T.A., Oganezova J.G., Anisimova V.V., Baeva A.B., Miaev D.H. Two-field mydriatic fundus photography to assess the prevalence of macular disorder in diabetes. Russian Journal of Clinical Ophthalmology. 2024;24(3):102–108 (in Russ.). DOI: 10.32364/2311-7729-2024-24-3-1.